Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Puri Saron Hotel Seminyak Kuta - Pramadivara, Ghosa; Seminari, Ketut (E-Jurnal Manajemen, 2014)
This Research to know influence of simultaneously and partial between quality of service which consist of physical evidence, reliability, responsiveness, guarantee, And empathy in Puri Saron Hotel Seminyak of Kuta to satisfaction of Consumer. Method data collecting with questioner and counted 95 participation, with method of purposive sampling, used data analysis of multiple regression.  Result of analysis (F test) that dimension of quality service have an impact on simultaneously to satisfaction of customer. Result of examination there are influence parsial between physical evidence, reliability, responsiveness, empathy and assurance to satisfaction of consumer at Puri Saron Hotel Seminyak of Kuta and dominant variable is physical evidence. Implication of Manajerial for Puri Saron Hotel Seminyak of Kuta can provide suggestion box and sigh so that can evaluate about excess and also insuffiency from quality of service Keyword : Quality of service, satisfaction of consumer.